A new kinetic Monte Carlo scheme with Gibbs ensemble to determine vapour–liquid equilibria. Issue 2 (22nd January 2017) - Tan, Shiliang Johnathan; Do, D. D.; Nicholson, D.
Abstract: We present a new kinetic Monte Carlo scheme, as an alternative to the Gibbs ensemble Monte Carlo ( GEMC ) method, to determine vapour–liquid equilibria using a canonical ensemble in a system composed of two boxes. To illustrate the method, we have tested it with two systems: (1) argon over a range of temperatures from below the triple point to close to the critical point; (2) methane and ethane mixtures of various compositions at 180 K. The advantage of the new scheme is that chemical potentials of all components are accurately determined in both boxes. In particular, the chemical potential in the liquid box is determined much more accurately than with the Widom method employed in conventional GEMC simulations.